rORAL: computational platform for the acquisition and remote assessment of images in oral health - Pinto, Ricardo Salgueiro Felgueiras (2018)
The evolution of mobile devices and their general availability creates an opportunity for their use in mobile health scenarios (mHealth). One of the possible use cases includes the use of mobile devices in capturing pictures to document clinical conditions. In oral care, this can be used to enable remote assessment of the oral cavity, for example, for oral health screening in the population. In this work we propose a digital platform to enable studies in oral care, which includes the capture of oral cavity photographs with mobile devices like smartphones, near the subject of care, and the posterior review by experts, using a web application. The proposed platform, named rORAL, consists in an Android application and two web applications. The Android application is used for image acquisition. One of the web applications is for studies management and the other is to manage worklists and to review the clinical cases. The system has been implemented in a functional prototype and was validated in the use case of oral care education with community practice